2008
DOI: 10.1016/j.talanta.2008.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of capsaicinoids from peppers

Abstract: The development of a rapid, reproducible and simple method of extraction of the majority capsaicinoids (nordihydrocapsaicin, capsaicin, dihydrocapsaicin, homocapsaicin and homodihydrocapsaicin) present in hot peppers by the employment of ultrasound-assisted extraction is reported. The study has covered four possible solvents for the extraction (acetonitrile, methanol, ethanol and water), the optimum temperature for extraction (10-60• C), the extraction time (2-25 min), the quantity of sample (0.2-2 g), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(98 citation statements)
references
References 30 publications
3
82
0
5
Order By: Relevance
“…It has been observed that sometimes the extraction yield could be improved by adding small percentages of water to the extraction solvent. [28][29][30] So, six different solvents concentration of 50, 60, 70, 80, 90, and 100% methanol have been studied for extracting pristimerin from Celastrus orbiculatus. The experimental parameters were set as follows: at 30°C for 20 min at 150 W of ultrasonic power with a S/S ratio of 20 mL/g.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that sometimes the extraction yield could be improved by adding small percentages of water to the extraction solvent. [28][29][30] So, six different solvents concentration of 50, 60, 70, 80, 90, and 100% methanol have been studied for extracting pristimerin from Celastrus orbiculatus. The experimental parameters were set as follows: at 30°C for 20 min at 150 W of ultrasonic power with a S/S ratio of 20 mL/g.…”
Section: Resultsmentioning
confidence: 99%
“…As variáveis estudadas foram potência ultrassônica e temperatura de processo tendo como resposta o rendimento global de extrato, calculado pela relação entre massa de extrato (g) por massa de matéria-prima alimentada em cada experimento (g). As condições de processo extremas, 600 W a 60 °C e 200 W a 40 °C respectivamente, foram comparadas com a técnica convencional de obtenção de capsaicinoides (BARBERO et al, 2008). Aproximadamente 1 g dos extratos obtidos foi pesado, diluído em metanol (Êxodo Científica), ajustado a um volume de 25 mL, e filtrado com o auxílio de filtrosmillex PVDF 0.22 µm (Millipore).…”
Section: Methodsunclassified
“…represent an important part of the fresh vegetable market in India, and are also signi icant worldwide in the segment of condiments, spices and salt preserves [1][2][3]. Among them, ive domesticated species have been globally recognized which includes C. annuum L., C. frutescens L., C. chinense Jacq., C. baccatum Jacq., and C. pubescens (4).…”
Section: Introductionmentioning
confidence: 99%